A SEISMIC SOURCE SUMMARY FOR SOVIET PEACEFUL NUCLEAR EXPLOSIONS - Sultanov D.D.; Rubinstein Kh.D.; Murphy J.R. (My University, 1999)
A summary of information is presented for 122 Soviet peaceful nuclear explosions (PNE) detonated during the 1965 to 1988 time period. The data presented include detonation times, locations, explosion yields, and depths of burial, as well as summary information regarding the explosion configurations and source emplacement media. This summary is intended to provide a concise reference for use in research studies of the seismic data recorded from this unique set of explosion sources.